2016
DOI: 10.1002/ecs2.1595
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of tree mortality in a temperate deciduous forest derived from a large forest dynamics plot

Abstract: Teixeira. 2016. Patterns of tree mortality in a temperate deciduous forest derived from a large forest dynamics plot.Ecosphere 7(12):e01595. 10. 1002/ecs2.1595 Abstract. Tree mortality is one of the most influential drivers of forest dynamics, and characterizing patterns of tree mortality is critical to understanding forest dynamics and ecosystem function in the present era of global change. Here, we use a unique data set of mortality in a temperate deciduous forest to characterize rates and drivers of mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 76 publications
(180 reference statements)
3
21
2
Order By: Relevance
“…Our results support the general observation that once the specieslevel growth-survival trade-off is accounted for, individual growth is positively correlated with survival (Clark & Clark, 1996;Wyckoff & Clark, 2000;R€ uger et al, 2011;Gonzalez-Akre et al, 2016). In a recent global meta-analysis, Cailleret et al (2017) found that trees that die typically grew less than conspecific survivors during the preceding 5-30 yr. A negative correlation between SA-RGR and mortality may result from: (a) a correlation between SA-RGR and the growth-survival trade-off (RGR, WD, mortality), or (b) a true causal relationship between SA-RGR (or an unmeasured factor correlated with SA-RGR, most likely carbon starvation) and mortality.…”
Section: Tree Mortality and Individual Growthsupporting
confidence: 86%
See 2 more Smart Citations
“…Our results support the general observation that once the specieslevel growth-survival trade-off is accounted for, individual growth is positively correlated with survival (Clark & Clark, 1996;Wyckoff & Clark, 2000;R€ uger et al, 2011;Gonzalez-Akre et al, 2016). In a recent global meta-analysis, Cailleret et al (2017) found that trees that die typically grew less than conspecific survivors during the preceding 5-30 yr. A negative correlation between SA-RGR and mortality may result from: (a) a correlation between SA-RGR and the growth-survival trade-off (RGR, WD, mortality), or (b) a true causal relationship between SA-RGR (or an unmeasured factor correlated with SA-RGR, most likely carbon starvation) and mortality.…”
Section: Tree Mortality and Individual Growthsupporting
confidence: 86%
“…Our results support the general observation that once the species‐level growth–survival trade‐off is accounted for, individual growth is positively correlated with survival (Clark & Clark, ; Wyckoff & Clark, ; Rüger et al ., ; Gonzalez‐Akre et al ., ). In a recent global meta‐analysis, Cailleret et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is consistent with our expectation that trees in valleys are less adapted to moisture stress, because valleys are generally wetter (Harms et al 2001, Itoh et al 2012, and suffer disproportionately during drought. These results suggest that tree dieback is largely associated with local fine-scale processes that differentiate water availability among habitats, which, in turn, may determine the aboveground biomass dynamics at the landscape scale (Valencia et al 2009, Gonzalez-Akre et al 2016, Levine et al 2016. One clear implication of these results is that data on tree Values are presented in Appendix S1: Table S1.…”
Section: Discussionmentioning
confidence: 89%
“…A future research priority is to determine specific environmental variables that drive fluctuations of tree species abundances in specific forests. Over the time period studied, the forest plots we examined were buffeted by a range of environmental factors, such as drought (Condit et al 1996), groundfires (Baker et al 2008), hurricanes/typhoons (Yap et al 2016;Hogan et al 2018) and insect herbivory (Gonzalez-Akre et al 2016). Although many such factors can be identified, they are often idiosyncratic in nature and often act on population abundances via nonlinear causal pathways.…”
Section: Discussionmentioning
confidence: 99%